Republic of Fiji : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that growth in the Fijian economy increased to 2u percent in 2012, supported by income tax cuts, low interest rates, and the one-time payouts under the Fiji National Provident Fund (FNPF) reform, which offset the negative impact of the severe floods and Cyclone Evan on the agriculture and tourist sectors. Inflation declined as imported commodity and food prices moderated. With a lower-than-budgeted deficit of 1 percent of GDP, Fiji's debt-to-GDP ratio continued to decline in 2012. The latest available indicators suggest accelerating growth momentum in the first half of 2013 boosted by increases in disposable income, bank borrowing, and rising investment.